EFL teacher self and collective efficacy scale (ETSCE): Developing efficacy measures in teaching EFL - Pratama, Raga Driyan; Imaniar, Fahmy; Lestari, Lies Amin; Anam, Syafi'ul; Rochmawati, Laila (Universitas Islam Negeri Banda Aceh, 2024)
This study aimed to develop a self- and collective efficacy measure for Indonesian EFL teachers focusing on teaching responsibilities, undertaken student advisory, coping English as classroom communication, English milieu, and institutional tasks. This study focused on demonstrating the development and validity of EFL Teacher Self- and Collective Efficacy Scale (ETSCE). The study used a quantitative research approach with cross-sectional survey research design. There were sixty-two EFL teachers involved in the study chosen using a voluntary sampling technique. Results showed that Content Validity Ratio (CVR) index was .5 with four panelists arguing valid with no revision. The internal consistency test showed a very highly reliable (α = .977) with no negative value in Inter-Item Correlation, which indicated all items measured the same underlying characteristics. Another result showed that all sub-scales in both self- and collective efficacy were categorized in a very highly reliable (α > .7) Therefore, the final ETSCE produced by this study is valid and reliable and can be a reference for those who have sought to study self- and collective efficacy in teaching EFL in Indonesia.